TEKTONICALLY CONTROLLED DRAINAGE NETWORKS: THE GEOLOGICAL HISTORY OF VOURAIKOS AND LADOPOTAMOS RIVERS (N. PELOPONESSUS - ΤΡΙΚΟΛΑΣ, Κ.; ΑΛΕΞΟΥΛΗ-ΛΕΙΒΑΔΙΤΗ, Α. (Bulletin of the Geological Society of Greece, 2005)
The geological research in the greater areas of Aigialia and Kalavryta resulted that neotectonic evolution occurred in two phases; the first one took place from Upper Miocene to Lower-Middle Pleistocene and the second from Lower-Middle Pleistocene up to now. The deposits and the flow direction of Vouraikos river are controlled by the neotectonic evolution of the region. During the first phase of neotectonic alteration in Lower Pleiocene - Lower Pleistocene, Vouraikos river deposited fluvial sediments of large width and extent, in the areas of M. Spilaio and Ano Diakopto in Kalavryta's ditch, and flowed into the greater area of Ano Diakopto - Akrata in marine or lacustrine environment. During the second phase (Lower-Middle Pleistocene till now), a part of the drainage network, lying south of Kalavryta's ditch, was detached and flowed southward to Aroanios's river.During Lower Pleistocene the flow direction of Vouraikos river progressively altered from its initial (pleicenic) NE direction, and turned westward at the part of M. Spilaio-Lofos village. The lower part of the basin, sited close to the estuaries, was detached and formed an individual basin. The central watercourse of Vouraikos river is formed by its older sediments, as well as in the Alpine background of this region. At the same period and up to Middle Pleistocene Vouraikos river deposits at Aigialias area a Gilbert' type deltaic fun of large width and extent, while in the area of Kalavryta deposits torrential sediments. During Middle Pleistocene Vouraikos river deposits κροκαλοτταγή of M.Spilaio's area. Ladopotamos flows eastward of Vouraikos river, in the sediments that Vouraikos river had deposit over the first phase of the neotectonic evolution. Ladopotamos was formed after Lower Pleistocene, during the second phase of the neotectonic evolution of the area in the abandoned northern part of Vouraikos basin which was developed by regressed erosion to the southern direction of the faults. The upper flow of the river was formed at the length of fault after Middle Pleistocene